Estilos de aprendizagem e educação a distância: um estudo dos estilos de profissionais do curso de especialização em saúde da família da Universidade Federal de São Paulo- UNIFESP - Natel, Maria Cristina [UNIFESP] (2014)
Learning through technology brings forth new ways of obtaining information and acquiring knowledge. Objective: The study herein aims to identifying the learning style of health professionals who attend the Specialization Course in Family Health at Universidade Aberta do Sistema Único de Saúde, Universidade Federal de São Paulo. Method: Quantitative approach to a study carried out to a convenience sample to map learning styles of health professionals. This sample has been designed to study the association of the variables such as gender (male and female), age in years and profession (nurse, physician and dentist) with each different learning style ( active, reflexive, theoretical and pragmatic). It has been inferred that the least prevalence found in the learning styles lies on 10% (0, 10) while the estimative error is 5% (0, 05) and the reliability level stands on 90% (or 10% significance level). SPSS® statistics program has examined the data of this study in univariate, bivariate and multivariate analyses. The learning style questionnaire Honey-Alonso – CHAEA has been used as the research tool. Result: The result regarding professional share in the sample indicated a predominance of nurses followed by dentists and then physicians. In the bivariate analysis, homogeneity has been identified regarding the share of learning styles. There is no relation between the variables age in years and learning styles. Concerning age by gender, a trend to younger women has been observed,and among nurses the number of women is higher than in other professions . In the multivariate analysis, it has been observed that physicians are associated with the reflexive style. Conclusion: This study has identified homogeneity regarding the share of learning styles, has revealed the correlation between the reflexive style and physicians, finally the predominance of nurses and a trend to younger women.